Estudo estrutural, morfológico, óptico e termoresistivo do sistema de PAni/PLA/ZnO depositado por solution blow spraying para aplicação como sensor de temperatura - Zárate, Raquel de Paula Llamoca (2022)
Advances in nanotechnology areas generate interest in producing materials that combine demands such as minimizing consumption, increasing performance, miniaturization, flexibility and sustainability. Among the target materials of studies, zinc oxide (ZnO) has been receiving a lot of attention, as it has a wide gap, high electronic mobility, thermal and electrical stability, and ease and versatility of processing. However, conductive polymers also entered the dispute in order to unite lightness, flexibility, transparency and also ease of processing. One of the main conductive polymers is Polyaniline (PAni) due to its easy processing and stability, formation of thin and homogeneous films, low cost and chemical stability. In addition to PAni, Poly (Lactic Acid), which is a biodegradable polymer, has been used together with Polyaniline to promote greater workability and mechanical resistance to this material. Based on this, the present work aims to obtain PAni/PLA/ZnO films at concentrations of 10, 20, 30, 40, 50 and 60% wt. of ZnO, through the technique of Solution Blow Spraying (SBSp), in order to evaluate its structural, morphological, optical and thermoresistive properties for application as a temperature sensor. The results confirmed obtaining PAni/PLA/ZnO films in the compositions proposed by the SBSp. method, which produced films with crystalline phases corresponding to ZnO and PAni. The morphological analysis showed a granular aspect for PAni and porosity, corresponding to the presence of ZnO ceramic. The decomposition temperatures were in the range of 200 to 400°C, according to thermogravimetry, showing that below this regime the films can present their thermoresistive properties without decomposing with temperature. The UV-VIS made it possible to identify and measure the gap, in the range of 2.32 to 3.92 eV, confirming values of a semiconductor, and that the presence of ZnO and PLA did not affect this property. Finally, the thermoresistive tests revealed a characteristic of a NTC (Negative Temperature Coefficient), proving that the PAni/PLA/ZnO films obtained in this work by the SBSp method have properties of a thermoresistor, therefore, they are promising for application as a temperature sensor at low temperatures.